2001
DOI: 10.1046/j.1365-2036.2001.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐minute 50 mg 13C‐urea breath test without test meal for the diagnosis of Helicobacter pylori infection in Chinese

Abstract: Background: We have previously shown that the 75 mg 13C‐urea breath test without citrate test meal is highly accurate for the diagnosis of Helicobacter pylori infection in Chinese subjects. A lower dose 50 mg 13C‐urea breath test protocol with a sampling time at 20 min has not been validated previously. Aim: To investigate the accuracy of a 20‐min 50 mg 13C‐urea breath test protocol in Chinese subjects. Methods: Consecutive dyspeptic patients referred for upper endoscopy were recruited. 13C‐urea breath test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 17 publications
(72 reference statements)
1
35
0
Order By: Relevance
“…From each study, the protocol with the best diagnostic performance was selected . Of these, 12 (30%) yielded sensitivities and specificities of 100% [33,37,43,45,47,56,61,63,65,[67][68][69] . Based on the results after reviewing the literature, the present study introduced several variations to simplify even further the technique and make it more cost-efficient, without compromising the high standards of sensitivity, specificity, positive and negative predictive values of the test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From each study, the protocol with the best diagnostic performance was selected . Of these, 12 (30%) yielded sensitivities and specificities of 100% [33,37,43,45,47,56,61,63,65,[67][68][69] . Based on the results after reviewing the literature, the present study introduced several variations to simplify even further the technique and make it more cost-efficient, without compromising the high standards of sensitivity, specificity, positive and negative predictive values of the test.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, doses of 125 [35,72] and 100 mg [36,40,47,48,51,54,57,60,62,65,[73][74][75][76][77][78][79][80][81][82][83] were validated by several American, European and Asian groups, and more recently 75 mg [32,37,[43][44][45]49,50,55,72,[84][85][86][87][88][89][90][91][92][93] , 50 mg [52,56,58,94,95] , 38 mg [96] , 25 mg and even 10 mg [69] of 13 C-urea have proved to be sufficient.…”
Section: Urea Dosementioning
confidence: 99%
See 2 more Smart Citations
“…Three other trials involving more than 300 patients studied in the pretreatment setting indicated that a dose of 50 mg of 13 C-urea, dispensed as a liquid solution or as a solid capsule, had sensitivity and specificity values greater than 95%. [8][9][10] One of these studies also evaluated the performance of 50 mg in the post-treatment setting, reporting sensitivity and specificity values of 100%. 10 In this study, we first evaluated the sensitivity and specificity of three breath tests, using 25, 15, and 10 mg of 13 C-urea, respectively, before eradication of H pylori.…”
Section: Discussionmentioning
confidence: 99%